High-potency multi-strain probiotic formulations for safety and improvement of gastrointestinal function and intestinal health: a randomized controlled clinical trial - Zhang, Xinru; Wu, Ying; Jiang, Yiru; Fan, Jiajia; Dong, Yao; Fang, Shuguang; Zhu, Jianguo; Gu, Shaobin (Frontiers in Nutrition, 2025)
BackgroundGastrointestinal dysfunction is a prevalent condition affecting approximately 20–40% of the global population, substantially impairing quality of life. Probiotics have been shown to improve gastrointestinal health by modulating the intestinal microbiota, enhancing epithelial barrier function, and regulating immune responses.MethodsIn this randomized controlled trial, 100 adults (aged 18–65 years) with gastrointestinal dysfunction, diagnosed according to the Citizen’s Intestinal Health and Hygiene Guidelines from the Expert Consensus on Precision Health Communication in China, were enrolled. Participants were randomly assigned to receive either Wec600B (2 sachets/day, 600 billion CFU/sachet, 1,200 billion CFU/day) or Wec1000B (2 sachets/day, 1,000 billion CFU/sachet, 2000 billion CFU/day) for 4 consecutive weeks. Safety outcomes, gastrointestinal symptom improvement rate, immune and inflammatory biomarkers, intestinal barrier function, and gut microbiota diversity were assessed before and after the intervention.ResultsAfter 4 weeks, both Wec600B and Wec1000B groups demonstrated significant improvement in gastrointestinal symptoms, including indigestion, abdominal pain, reflux, constipation, and diarrhea, without reported adverse events. Levels of fecal calprotectin (FC), neutrophil gelatinase-associated lipocalin (NGAL), and the pro-inflammatory marker FL were reduced, along with intestinal injury indicators such as diamine oxidase (DAO), D-lactic acid (D-LA), and lipopolysaccharide (LPS). In contrast, secretory IgA levels increased. Gut microbiota analysis revealed a significant increase in the relative abundance of beneficial genera, including Bifidobacterium, Lactobacillus, Blautia, and Collinsella, and a decrease in potentially pathogenic genera such as Prevotella, Escherichia-Shigella, and Klebsiella.ConclusionBoth Wec600B and Wec1000B high-potency probiotics improved gastrointestinal symptoms and enhanced intestinal health, likely through modulation of gut microbiota composition, reduction of inflammation, and reinforcement of intestinal barrier function.